Taste preference, food neophobia and nutritional intake in children consuming a cows' milk exclusion diet: a prospective study. Issue 6 (14th June 2016) - Maslin, K.; Grimshaw, K.; Oliver, E.; Roberts, G.; Arshad, S. H.; Dean, T.; Grundy, J.; Glasbey, G.; Venter, C.
Abstract: Background: Taste exposure in infancy is known to predict food preferences later in childhood. This is particularly relevant in children with cows' milk allergy who consume a substitute formula and/or a cows' milk exclusion (CME) diet early in life. This prospective study aimed to show whether there is a long‐term effect of consuming a substitute formula and CME diet on taste preferences and dietary intake. Methods: Children were predominantly recruited from two large birth cohort studies in the UK. Two groups were recruited: an experimental group of children who had consumed a CME diet during infancy and a control group who had consumed an unrestricted diet during infancy. Parents completed a food neophobia questionnaire and an estimated prospective food diary. Children completed a taste preference test and their growth was assessed. Results: One hundred and one children with a mean age of 11.5 years were recruited (28 CME and 73 controls). Children in the CME group had a significantly higher preference for bitter taste than those in the control group ( P < 0.05). There were significant differences between the groups with respect to the intake of some micronutrients, including riboflavin, iodine, sodium and selenium. Food neophobia did not differ between groups. Some 28% of the CME group were overweight/obese compared to 15% of the control group; however, this difference was not statistically significant. Conclusions: Consuming a substitute formula and/or a CME diet in infancy has a long‐term effect on the preference for bitter taste. Differences exist with respect to the intake of some micronutrients, but not macronutrients. There was a nonsignificant trend towards being overweight and obese in children in the CME group.